2021
DOI: 10.1088/1748-9326/abe2cd
|View full text |Cite
|
Sign up to set email alerts
|

Slowdown and reversal of terrestrial near-surface wind speed and its future changes over eastern China

Abstract: A recovery of near-surface wind speed (SWS) in the last decade has been reported over China; nevertheless, the contributions of large-scale ocean-atmosphere circulations (LOACs) to the SWS changes are rarely investigated. In this study, the turning point (TP) of the terrestrial stilling was validated over eastern China for 1979–2017. Furthermore, a forward stepwise regression algorithm was used to assess the contribution of LOACs to SWS changes. The results revealed that the TP of the SWS reversal occurred in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…These findings suggest that in recent years, the global wind speed also has had a weak mean state and variability. Many previous studies have suggested that large‐scale circulations and urbanization are important factors to the observed wind stilling 40,68–70 . The Siberian high pressure impacts the NWS variation on the decadal timescale by influencing weather regime occurrence over Eastern Asia 68 .…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings suggest that in recent years, the global wind speed also has had a weak mean state and variability. Many previous studies have suggested that large‐scale circulations and urbanization are important factors to the observed wind stilling 40,68–70 . The Siberian high pressure impacts the NWS variation on the decadal timescale by influencing weather regime occurrence over Eastern Asia 68 .…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Many previous studies have suggested that large-scale circulations and urbanization are important factors to the observed wind stilling. 40,[68][69][70] The Siberian high pressure impacts the NWS variation on the decadal timescale by influencing weather regime occurrence over Eastern Asia. 68 As for urbanization, it ignored in the regional NWS decline, but it does not play a dominant role.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this paper, the wind speed change mechanisms in China are analyzed from two aspects: upper wind elds and uneven warming between high and low latitude zones. In addition to the above two aspects, the variation of near-surface wind speed may be closely related to the aerosol forcing and land use changes (Deng et al 2021a), urbanization (Wang et al 2020), larger-scale ocean-atmosphere circulations (Zha et al 2021), Arctic Oscillation (AO) (Ge et al 2021), etc. In the future, it would be of great signi cance to study the variation mechanisms of near-surface wind speed in China from various aspects, and to quantitatively identify the main in uencing factors of near-surface wind speed variations in different periods and regions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the overall tend of surface wind speed in China is weakening, and there are obvious seasonal, regional and wind speed segment differences in surface wind speed [45][46][47] . The study found that in recent 50 years, the annual wind speed in different regions of Northeast China is obviously different.…”
Section: Discussionmentioning
confidence: 99%